A Nile blue based infrared fluorescent probe: imaging tumors that over-express cyclooxygenase-2. Issue 4 (26th November 2014) - Wang, Benhua; Fan, Jiangli; Wang, Xianwu; Zhu, Hao; Wang, Jingyun; Mu, Huiying; Peng, Xiaojun
Abstract : The freeNiblue-C6-IMC exists in a folded conformation where fluorescence is quenched, and when it binds to COX-2 in the Golgi apparatus of cancer cells, it is forced to adopt the unfolded state, and then fluorescence is turned on.Niblue-C6-IMC was proved to specifically target COX-2 by native polyacrylamide gel electrophoresis analysis. Abstract : The first Golgi-localized cyclooxygenase-2 (COX-2)-specific near-infrared (NIR) fluorescent probe, Niblue-C6-IMC, able to detect cancer cells, was designed. Importantly, Niblue-C6-IMC preferentially labeled the tumors in a mouse tumor model with deep tissue penetration capacity. It may be a promising molecular tool for guiding tumor resection during surgery.